Sociology - Pintar, Judith
This balanced, mainstream, beautifully written and totally up-to-date text is unrivalled in its ability to get students to see the connection between themselves and the social world. It teaches students how to think sociologically, not just what to think, and emphasizes the importance of diversity and a global perspective. It has been heralded for its inclusion of pop culture examples that instantly connect with today's students, and for its presentation of sociological concepts in a fresh, contemporary light